خیراتی کاموں کے مقاصد قرآن وحدیث کی روشنی میں تجزیاتی مطالعہ : Objectives of charitable works Analytical study in the light of Quran and Hadith - Sarwar, Muhammad Saleem; Rizwan, Dr.Muhammad (Al-Amīr Research Journal for Islamic Studies, 2023)
Islam is a complete religion. It not only teaches the rights of Allah but it also gives special importance to the rights of humanity. Its aim is to give respect and dignity to the lives of poor and deprived people of the society in the light of the Holy Quran and Sunnah. The privileged people of the society have made different organizations and societies to help the underprivileged and make them independent. Through self-help, pious people made wells, roads, hospitals, madrassas, in order to help the poor and This article is an introductory study of that knowledge and in the article significance and essentiality of the purposes of shariah have been explained after detailed interpretations of these purposes. Opinions of ancient and modern experts of the concerned field of knowledge have also been incorporated. Finally, various types of objectives of shariah have been debated. Keywords: Charitable works, Islam, Complete code, Pious people.